Differences in sex distribution, anatomic location and MR imaging appearance of pediatric compared to adult chordomas. Issue 1 (December 2016) - Sebro, Ronnie; DeLaney, Thomas; Hornicek, Francis; Schwab, Joseph; Choy, Edwin; Nielsen, G.; Rosenthal, Daniel
Abstract Background Chordomas are rare malignancies that primarily affect adults, but also rarely affect pediatric patients. We compared the imaging appearance, demographic and anatomic distributions of adult and pediatric chordomas in a large cohort. Methods We performed a retrospective review of medical records of 220 subjects with histologically confirmed chordomas of the axial skeleton and pre-treatment magnetic resonance imaging studies. Age, sex, type of chordoma (conventional, chondroid or dedifferentiated), the anatomic location of the chordoma, as well as whether the lesion was primarily extra-osseous were recorded. Pediatric subjects were less than 21 years at the time of diagnosis. Binomial two-sample tests of proportions and Fisher's exact tests were used to compare proportions between the pediatric and adult subjects. Results Fifty six pediatric subjects (58.9 % female) and 164 adult subjects (42.1 % female) were identified. The proportion of female subjects with chordomas was significantly higher in the pediatric cohort compared to the adult cohort (P  = 0.04). Most chordomas occur in Caucasians, however African-Americans were more represented in the pediatric cohort than in the adult cohort (P  = 0.01). 69.6 % (39/56) of the pediatric chordomas involved the clivus/skull base and cervical spine compared to 29.3 % (48/164) of the adult chordomas (P  = 1.99 × 10−7 ). Only 1.8 % (1/56) of the pediatric chordomas was in the sacrococcygeal region compared to 36.0 % (59/164) of the adult chordomas (P  = 2.55 × 10−8 ). In cases where pre-treatment imaging was available, 93.8 % (16/17) of pediatric chordomas were predominantly extra-osseous compared to 76.7 % (46/60) of adult chordomas (P  = 0.17). Conclusions Pediatric chordomas more often affect females and occur most frequently at the craniocervical junction with decrease in incidence distally in the spine, whereas adult chordomas most frequently involve the craniocervical and sacrococcygeal regions.